Experimental and applied mechanics. proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics. Volume 4 : ([2016]) - Unknown
No abstract available